Biochar combined with organic and inorganic fertilizers promoted the rapeseed nutrient uptake and improved the purple soil quality - Liu, Ming; Linna, Cholidah; Ma, Shumin; Ma, Qun; Song, Wenfeng; Shen, Mingzhu; Song, Lixia; Cui, Kaidong; Zhou, Yuling; Wang, Longchang (Frontiers in Nutrition, 2022)
Biochar is a kind of organic matter that can be added into soil to improve soil quality. To study the effect of biochar combined with organic and inorganic fertilizers on rapeseed growth and purple soil fertility and microbial community, a completely randomized block design was designed with three levels of biochar (B0: no biochar, B1: low-rate biochar, B2: high-rate biochar); two levels of inorganic fertilizers (F1: low-rate inorganic fertilizer; F2: high-rate inorganic fertilizer); and two levels of organic fertilizers (M1: no organic fertilizer; M2: with organic fertilizer). All combinations were repeated three times. The combined application of biochar and organic and inorganic fertilizers could improve soil pH, soil fertility and soil microbial community richness: The pH of B1F2M1 increased 0.41 compared with the control, the nitrogen, phosphorus and potassium content increased by 103.95%, 117.88% and 99.05%. Meanwhile, soil microbial community richness was also improved. Our research showed that biochar could promote the Nutrient Uptake of rapeseed, and the combined application of biochar with organic and inorganic fertilizers could improve soil fertility and increase microbial diversity. Low-rate biochar combined with organic fertilizer and low-rate inorganic fertilizer was the most suitable application mode in rapeseed production in purple soil area of Southwest China.